Growth, photosynthesis, and reactive oxygen system responses of allotriploid Populus cathayana to salt stress - T. QIU; Y. WANG; X.N. GENG; Y. ZHANG; Y. LI; X.Y. KANG (Photosynthetica, 2020)
Polyploid plants are generally considered to have a high stress resistance. In this study, two full sibling allotriploid populations (FDR and SDR) with different 2n female gamete sources and one diploid population (2N) obtained from the same Populus cathayana parents were investigated. We compared the growth morphology, photosynthetic parameters, peroxidase activity and proline contents after salt stress. The results showed that the salt tolerance of the triploid poplar population was higher than that of the diploid population. And there were some differences between the genotypes of the triploid and diploid populations under salt stress. The genotypes with the higher salt tolerance in the triploid populations were much more tolerant than those with the higher salt tolerance in the diploid populations. There was no significant difference in salt tolerance between the FDR and SDR triploids.